Europe Needs to Integrate Immersive Learning Quickly at All Education Levels – But How? What to Learn From 25 EU Projects in This Field - Schwaiger, Michael (Journal of Elementary Education, 2021)
Manifold technical developments have allowed immersive technologies - virtual (VR) and augmented (AR) realities and their fusion to mixed or extended reality (MR/XR) - to find their way into many areas of life and work. Given their almost infinite creative possibilities, they are also of great interest for pedagogy. But what are the possibilities and where are the limits, and where does Europe stand in this respect at all? To find answers, we have evaluated 25 EU projects dealing with VR/AR/XR-based learning.